Association of HLA class II DR/DQ alleles in children and adolescents with rheumatic heart disease from a tertiary care centre in North India - Anbarasan A; Dinesh kumar; Rakesh deepak; Dheeraj deo bhatt; Lata kumari; Praveen Arumugam; Kawaldeep kaur; Likhith kumar s (Indian Heart Journal, 2023)
Introduction: Rheumatic fever and RHD constitutes an important public health problem in India. The relatively low attack rate of RF, the high concordance rate for RF in monozygotic twins (19%) compared to dizygotic twins (2.5%), and the high familial incidence of RF suggest the involvement of host genetic factors in susceptibility to RF with consequential progression to RHD. Objective: To study the association of HLA CLASS II DR/DQ alleles in children and adolescents with RHD from a tertiary care center in North India. Methods: 30 RHD patients and 30 age and sex-matched controls were included in our study and blood samples for HLA typing were processed through LAB Type™ reverse SSO DNA typing method. The assignment of the HLA typing was based on a comparison with already published HLA gene sequences. Results: The mean age of RHD patients and matched control groups were 12.97 ± 2.95 and 11.93 ± 3.23, respectively. In the cases and control group, males accounted for 63.3% and 50% of the patients respectively. A significant difference was found between the cases and controls for HLA DR∗ 15 (p-value 0.002), HLA DR∗ B4 (p-value 0.045), HLA DR∗ B5 (p-value 0.017), and HLA DQB1∗ 02 (p-value 0.005). Conclusion: Our study suggests that HLA class II haplotypes may provide insight into the molecular mechanism of RHD and be a useful tool in predicting the clinical outcome in RF patients, thereby affording new means of intervention or vaccine design. Larger studies are needed to address this in our population.